Microplastic detectives: a citizen-science project reveals large variation in meso- and microplastic pollution along German coastlines - Bruno Andreas Walther; Franco Pasolini; Franco Pasolini; Špela Korez Lupše; Melanie Bergmann (Frontiers in Environmental Science)
Plastic production and plastic waste have increased to such an extent that it has become globally ubiquitous. Several studies already have investigated the meso- and microplastic pollution along the German Baltic and North Sea coasts, but were all limited to a few locations. To obtain representative bulk samples from sandy beaches along the entire German coast, we initiated a citizen-science project entitled “Microplastic Detectives.” Here, we describe in detail 1) how we recruited, instructed, and engaged citizen scientists, 2) why we chose bulk sampling over reduced-volume sampling, and 3) the laboratory methods we used. The citizen scientists collected 1,139 samples from 71 locations along the German coast, totalling 2.2 tons of sand. After drying, sieving with a 1 mm sieve, and visual inspection of the retained fraction under a binocular microscope, all putative plastic particles ≥1 mm were analysed by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. 177 out of 1,139 samples (15.5%) contained a total of 260 plastic particles, with a large right-skewed variation among locations. Most of the particles were fragments, foils, foams, fibres, and pellets (96.2% in total), and 89.6% of the particles were made of polyethylene, polypropylene, polyester, and polystyrene. The unweighted mean pollution densities were 4.12 particles m−2, 0.17 particles kg−1 and 0.27 particles L−1, and the weighted mean pollution densities were 3.77 particles m−2, 0.11 particles kg−1 and 0.18 particles L−1. These densities are lower than in other similar studies, but previous studies had important methodological differences. We discuss how these differences could have influenced the results and make recommendations for improving future studies. Two important recommendations are 1) to use random or stratified random sampling and 2) to run transects perpendicular (rather than parallel) to the waterline. Our study highlights that large-scale, scientifically rigorous monitoring of meso- and microplastic pollution is possible at the national level, and possibly even at much larger spatial and temporal scales. With the help of local authorities, such a monitoring program could be established.